Synthesis and Porous Structure Characteristics of Allyl Methacrylate/Divinylbenzene Polymers - Duranoglu, Dilek; Trochimczuk, Andrzej W. (MDPI, 2024)
A set of six porous copolymers of allyl methacrylate (AllMeth) and divinylbenzene (DVB), containing 5 to 50 wt% of the latter crosslinker, are synthesized by suspension polymerization method in the presence of inert diluents. Obtained polymers have various specific surface areas-those with 20 to 50 wt% of DVB have a high surface area in the range of 410-480 m2/g, depending only slightly on the amount of the aromatic crosslinker. Specific surface area decreases strongly only when DVB content is 15 and 5 wt%. That is the feature that is unusual for crosslinked polymers and indicates the participation of allyl groups in making a novel polymeric network of high porosity. All polymers contain polar carbonyl groups, with an electron pair able to interact with polar sorbates. Polymers are characterized using elemental analysis, FTIR, and their porous structure is characterized by nitrogen adsorption at 77 K. All polymers contain residual allyl groups, which possibly can serve as convenient points for chemical modification, allowing for the future synthesis of specialty polymers (such as ion-exchangers and coordinating resins).
Keywords: polar polymers; highly crosslinked polymers; specific surface area; SOLID-PHASE EXTRACTION; SORPTIVE PROPERTIES; PHENOLIC-COMPOUNDS; AROMATIC-COMPOUNDS; HAMMETT EQUATION; POLAR COMPOUNDS; RESIN; ADSORPTION; COPOLYMERS; SORBENTS; Polymer Science